Ischemia-modified albumin in type 2 diabetic patients with and without peripheral arterial disease (Clinics, 2011)
OBJECTIVE: To determine whether there is an association between serum ischemia-modified albumin and the risk factor profile in type 2 diabetic patients with peripheral arterial disease and to identify the risk markers for peripheral arterial disease. METHODS: Participants included 290 patients (35.2% women) with type 2 diabetes. The ankle-brachial pressure index was measured using a standard protocol, and peripheral arterial disease was defined as an ankle-brachial index